Tree islands memengaruhi interaksi tritrofik antara tanaman, herbivor, dan parasitoid pada habitat perkebunan sawit di Desa Bungku, Jambi, Sumatra: Tree islands alter tritrophic interactions among plants, herbivore, and parasitoids in oil palm habitats in Bungku Village, Jambi, Sumatra - Permatasari, Gusthi Ayu; Hidayat, Purnama; Kasmiatun; Azhar, Azru; Buchori, Damayanti (Perhimpunan Entomologi Indonesia, 2025)
Tritrophic interactions refer to interactions among three trophic levels within a community (producers, herbivores, and carnivores). In oil palm ecosystems, these three trophic levels consist of (1) vegetations, (2) Lepidopterans as herbivores, and (3) Hymenopterans and some of Dipterans as carnivores. Vegetation complexity often influences trophic levels within the food web. This study aimed to investigate the influence of tree island in oil palm plantation on tritrophic interaction, parasitism and abundance of natural enemies. The research was conducted in oil palm plantations which had been enriched with several tree species to form tree islands. Six tree species Peronema canescens, Shorea leprosula, Dyera polyphylla, Parkia speciosa, Archidendron pauciflorum, and Durio zibethinus were planted in different combinations within plots of various sizes (5 m × 5 m, 10 m × 10 m, 20 m × 20 m, and 40 m × 40 m). There were three enrichment combinations within the tree islands, i.e., one plant species, six plant species, and control (without enrichment). The results showed that adding tree species in oil palm plantations influenced herbivore species richness and increased the presence of generalist parasitoids. The parasitism rate of Lepidoptera pests was affected by the tree species planted but not by the number of tree species. Parasitoid abundance was not affected by the number of tree species. Overall, this study indicated that the tree islands might increase the complexity of food webs; however,it was not necessarily followed with increased parasitoid abundance nor functional role in oil palm plantations.